2008
DOI: 10.1209/0295-5075/82/54003
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of EIT window by incoherent pumping in a three-level Λ system: Effect of homogeneous and inhomogeneous broadening

Abstract: The interplay between dynamically induced coherence (DIC) and spontaneously generated coherence (SGC) can induce electromagnetically induced transparency (EIT) in a threelevel closed Λ system. When the contributions from these two coherences are equal in magnitude and opposite in sign at the resonances of both the coherent and probe fields, transparency of the probe light occurs at the resonance with absorption humps away from the resonance. We have demonstrated here that the broadening of the EIT window can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Previously we have demonstrated that the broadening of the EIT window can be controlled by changing the strength of incoherent pumping. This is a new approach for achieving a wide EIT window for lossless and distortionless transmission of light of a large spectral width [41]. Here we will show that an incoherent pump can control the realization of negative refraction in different spectral regions.…”
Section: Theoretical Modelmentioning
confidence: 77%
See 2 more Smart Citations
“…Previously we have demonstrated that the broadening of the EIT window can be controlled by changing the strength of incoherent pumping. This is a new approach for achieving a wide EIT window for lossless and distortionless transmission of light of a large spectral width [41]. Here we will show that an incoherent pump can control the realization of negative refraction in different spectral regions.…”
Section: Theoretical Modelmentioning
confidence: 77%
“…To show the importance of the effect of SGC for achieving simultaneous negative real values of r and r , we have calculated Re( r ) and Re( r ) in the absence of SGC. Previously we have proposed a scheme for experimental realization of EIT considering SGC in the LiH molecular system [40] and have shown how the group velocity can be controlled by controlling the incoherent pump rate in the band of positive refraction [41]. Here we will show how the negative refraction in the LiH molecular system can be realized and the group velocity can be controlled from superluminal to subluminal in this band of negative refraction.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, most of these can be tuned by mechanical alignment making it difficult to realize the dynamic control of the transparency window, which limits the practical application of EIT-like effect. In addition to a three-level type configuration [22], EIT has also been realize in various multilevel configurations [23][24][25][26], and quite recently, it was extended to the N and (N+1)-level systems [27,28]. These systems exhibited multiple EIT with interest in the bifurcation of quantum information in multiple channels Garido Alzar et al [27] reproduced the EIT behavior experimentally using two linearly coupled LRC circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic coherence effects manifest themselves in a wealth of phenomena whose study is a topic of current interest in quantum optics and laser physics. Among these phenomena we find amplification and lasing without inversion (AWI and LWI) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], coherent population trapping (CPT) [18][19][20][21][22], electromagnetically induced transparency (EIT) [18,[23][24][25][26], enhancement of refractive index with vanishing absorption [27][28][29][30] and sub-Poisonian photon statistics of light emitted by laser operation without population inversion [31][32][33][34][35][36][37][38][39]. Among these effects amplification and lasing without the requirement of population inversion has received considerable interest due to its potential capability of obtaining short wavelength lasers in the UV and x-ray spectral domains.…”
Section: Introductionmentioning
confidence: 99%